Role of proteolysis in development of murine adipose tissue - Christiaens, Valerie; Scroyen, Ilse; Lijnen, H. Roger (Thrombosis and Haemostasis, 2008)
Obesity is a common disorder, and related diseases such as diabetes, atherosclerosis, hypertension, cardiovascular disease and cancer are a major cause of mortality and morbidity inWesterntype societies. Development of obesity is associated with extensive modifications in adipose tissue involving adipogenesis, angiogenesis and extracellular matrix proteolysis. The fibrinolytic (plasminogen/plasmin) and matrix metalloproteinase (MMP) systems cooperate in these processes. A nutritionally induced obesity model in transgenic mice has been used extensively to study the role of the fibrinolytic and MMP systems in the development of obesity. These studies support a role of both systems in adipogenesis and obesity, and suggest that modulation of proteolytic activity may affect development of adipose tissue.
Keywords: Animal models; fibrinolysis inhibitors; gene knock-out; matrix metalloproteinases; obesity